IMPROVING GRADE 9 SCIENCE PROCESS SKILLS OF SMPN 5 PROBOLINGGO USING DISCOVERY LEARNING MODEL - Yuli Astuti (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2019)
Science process skills are important for students when learning science and their applications in everyday life because through a series of process skills, the knowledge gained becomes more meaningful and, in the end, students have a way of thinking and doing activities as a scientist through the scientific method. In reality, the science's students process skills have not been maximal, especially in formulating problems and hypotheses. This research is a Class Action Research conducted with two cycles consisting of the stages of planning, implementation, observation, and reflection. The research subjects were grade 9 students of IXA class of SMPN 5 Probolinggo. Data collection using documentation, observation, and test methods. The data in this study include learning implementation data and science process skills of students. The results of this study indicate that discovery learning can improve the science process skills of students in the IXA class of SMP Negeri 5 Probolinggo. The percentage of learning implementation increased from 88.87% to 97.92%, while the students science process skills increased from 73.50% to 96.50%.Keywords: science process skills, classroom action research, discovery learning